KAJIAN PROGRAM KELUARGA HARAPAN DALAM MEWUJUDKAN KEMANDIRIAN EKONOMI MASYARAKAT DESA TOMBULILATO KECAMATAN BONE RAYA KABUPATEN BONEBOLANGO - Nur Eng Mokodompit (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2019)
The aim of this research was to determine the improvement of quality life that very poor households receiving the family hope program in Tombulilato Village, Bone Raya District. The type of research used is qualitative research, which is based on actual facts or situations and conditions. In this research is the main focus of researchers was the poor, especially those who received the Harapan Family program. The results of this research were that all research informants stated relatively the same attitudes and answers that there were significant differences in the quality of life of the children who received the benefits of education before receiving PKH assistance and after the family hope program. Where children can enjoy good education and get good report cards too. The suggestion is that the cooperation of related departments is needed in providing program socialization to recipient participants and companions of this Family Hope Program (PKH). In particular, the Ministry of Education and the Ministry of Health (at least teaching staff or school principals and the health center in this case midwives), so that there is mutual strength in implementing this hope family program so that it is truly on target in an effort to achieve MGDs targets.Keywords : PKH, Implementation, MGDs targets.